Prioridades para a conservação de Butia (Arecaceae) - Eslabão, Marcelo Piske; Ellert-Pereira, Paulo Eduardo; Barbieri, Rosa Lía; Heiden, Gustavo (Ciência Florestal, 2022)
Butia (Arecaceae) is a palm genus of 21 South American species. The factors that determine the geographical distribution and conservation status of Butia species are still poorly understood. We mapped the specimens with a natural occurrence in South America and evaluated the state of conservation of the species and their respective threat criteria. These results allowed the proposition of priorities for in situ and ex situ conservation. Eleven species were evaluated as Vulnerable (VU), five species as Critically Endangered (CR), three species as Endangered (EN), one species was assessed as Near Threatened (NT) and one species could not be assessed due to Deficient Data (DD). Eight priorities for in situ conservation are recognized and seven species are considered as priorities for ex situ conservation and germplasm collection. The results support the choice of priority areas for in situ conservation and sustainable management, and strategies for ex situ conservation of the species and germplasm collection.